2007
DOI: 10.1515/jpem.2007.20.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Status in Children with Congenital Adrenal Hyperplasia

Abstract: Congenital adrenal hyperplasia (CAH) is caused by a deficiency in an adrenal enzyme resulting in alterations in Cortisol and aldosterone production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
2
25
1
Order By: Relevance
“…In children and young adults, bone mineral density (BMD) was reported to be increased (4), normal (5,6), or decreased (7). Other pediatric studies found decreased BMD in males (8), in long-term treated girls (9), and at puberty (10).…”
Section: Introductionmentioning
confidence: 99%
“…In children and young adults, bone mineral density (BMD) was reported to be increased (4), normal (5,6), or decreased (7). Other pediatric studies found decreased BMD in males (8), in long-term treated girls (9), and at puberty (10).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that osteoporosis risk is higher in adult patients with CAH compared to the normal population (6)(7)(8)(9). However, in younger CAH patients there are contradictory results in published studies and case reports that reported that BMD values were not changed or decreased (10)(11)(12)(13)(14)(15)(16)(17)(18). This situation may be related to smaller numbers of patients, extensive range of age distribution, and heterogeneous glucocorticoid dose among groups.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained using calcaneal quantitative ultrasonometry [Stikkelbroeck et al, 2003] and lumbar QCT [Elnecave et al, 2008]. Normal results have been found both in women with CAH [Guo et al, 1996;Mora et al, 1996;Stikkelbroeck et al, 2003] and in girls or female adolescents [Gussinyé et al, 1997;Fleischman et al, 2007;Elnecave et al, 2008, Sahakitrungruang et al, 2008. Conversely, markedly reduced bone mass measurements have been described in other studies [Cameron et al, 1995;Jääskeläinen and Voutilainen, 1996;Girgis and Winter, 1997;Hagenfeldt et al, 2000;Paganini et al, 2000;de Almeida Freire et al, 2003;King et al, 2006;Sciannamblo et al, 2006;Bachelot et al, 2007;Falhammar et al, 2007;Chakhtoura et al, 2008;Zimmermann et al, 2009].…”
Section: XX Dsd: Bone Health In Cahmentioning
confidence: 52%
“…Several studies demonstrated that bone mass measurements of the lumbar spine [Mora et al, 1996;Gussinyé et al, 1997;Stikkelbroeck et al, 2003;Fleischman et al, 2007;Elnecave et al, 2008, Sahakitrungruang et al, 2008, femoral neck [Stikkelbroeck et al, 2003;Fleischman et al, 2007] and the whole skeleton [Guo et al, 1996;Mora et al, 1996;Fleischman et al, 2007;Elnecave et al, 2008, Sahakitrungruang et al, 2008 did not differ significantly from those of healthy controls or reference values. Similar results were obtained using calcaneal quantitative ultrasonometry [Stikkelbroeck et al, 2003] and lumbar QCT [Elnecave et al, 2008].…”
Section: XX Dsd: Bone Health In Cahmentioning
confidence: 99%
See 1 more Smart Citation